OPTIMASI ENERGI PADA CLINKER GRATE COOLER DI INDUSTRI SEMEN - Fajar Ramadhan; Yanti Suprianti (Steam Engineering, 2023)
The clinker cooling process within the cement cooler is a highly significant aspect of cement production. It not only impacts the quality of clinker but also plays a role in heat recovery to reduce fuel consumption in the kiln and preheater. In the cement industry, energy usage is divided into 78% electricity and 22% thermal energy, with almost all thermal energy consumption occurring during the clinker production process (preheater, kiln, and cooler). The performance of the clinker cooler is indicated by the value of the recovery efficiency under existing conditions, which is 69.3%, falling below the standard range of 70-75%. Energy conservation efforts in the cement industry involve utilizing the heat generated from the clinker cooling process as a supply of combustion air for the kiln and preheater. The Reduced Fall Through (RFT) type grate plate system with compartments is unable to properly control the flow of cooling air from the cooling fan to the clinker bed surface. To optimize the cooling process and heat recovery, a redesign of the clinker cooler is carried out by replacing the RFT type grate plate with a Control Flow Grate (CFG) type in compartments five, located in rows 43 to 48. Simulations are employed to support this analysis and design, utilizing ANSYS 18.2. The goal of these simulations is to assess airflow parameters and heat transfer. The clinker cooler recovery efficiency under existing conditions is 69.3%. However, following the technological design process, the efficiency performance increases to 72.9%.